Enhanced performance of p-type SnOx thin film transistors through defect compensation. (5th October 2022) - Zhang, Wei; Hong, Ruohao; Qin, Wenjing; Lv, Yawei; Ma, Jianmin; Liao, Lei; Li, Kenli; Jiang, Changzhong
Abstract: Due to the unique outermost orbitals of Sn, hole carriers in tin monoxide (SnO) possess small effective mass and high mobility among oxide semiconductors, making it a promising p-channel material for thin film field-effect transistors (TFTs). However, the Sn vacancy induced field-effect mobility deterioration and threshold voltage ( V th ) shift in experiments greatly limit its application in complementary metal-oxide-semiconductor (CMOS) transistors. In this study, the internal mechanism of vacancy defect compensation by aluminum (Al) doping in SnO x film is studied combining experiments with the density functional theory (DFT). The doping is achieved by an argon (Ar) plasma treatment of Al2 O3 deposited onto the SnO x film, in which the Al2 O3 provides both the surface passivation and Al doping source. Experimental results show a wide V th modulation range (6.08 to −19.77 V) and notable mobility enhancement (11.56 cm 2 V −1 s −1 ) in the SnO x TFTs after the Al doping by Ar plasma. DFT results reveal that the most possible positions of Al in SnO and SnO2 segments are the compensation to Sn vacancy and interstitial. The compensation will create an n-type doping effect and improve the hole carrier transport by reducing the hole effective mass ( m h *), which is responsible for the device performance variation, while the interstitial in the SnO2 segment can hardly affect the valence transport of the film. The defect compensation is suitable for the electronic property modulation of SnO towards the high-performance CMOS application.